RESPONSE REACTIONS STUDY OF THE ORAL TISSUES TO THE DENTAL ALLOYS - Adina Oana Armencia; Loredana Liliana Hurjui; Irina Grădinaru; Ion Hurjui; Claudia Cristina Tărniceriu; Mihaela Mitrea; Dana Baciu; Irina Bamboi; Carina Balcoș (Romanian Dental Association for Education, 2021)
Aim of the study: the study on the allergic, inflammatory and toxic reactions of the dental alloys. Material and method: Oral clinical examination followed the presence of reactions due to some release elements in the oral environment. Morphopathological examination allowed to assess the reactivity of oral tissues who were in direct contact with dental materials. Results: the subjective symptoms incriminated was: metallic taste, burning sensations, decrease in taste sensitivity, etc. association with general status. Objective symptoms was: allergic, inflammatory, and chimico-toxic mechano-iritative reactions. Mophopatologic examen show atrophic aspects of oral mucosa with decrease dimension and papiles brides, or hipertrophic aspect, with inflammatory infiltration in the corion and distrophic lesions with to break off epithelium integrity. Conclusions: metallic restorations may determine unfavorable interactions between alloys and oral adjacent structures with severe clinical implications.